Fasies Sedimen Kuarter Kaitannya Dengan Potensi Likuefaksi Di Kawasan Das Cimanuk, Indramayu, Jawa Barat - Rifki Asrul Sani; Eko Soebowo; Imam A. Sadisun (Jurnal Teknologi, 2022)
The lower Cimanuk catchment area which will be developed as industrial area is dominated by Quaternary deposits which are susceptible againts liquefaction if large earthquakes occurred. The presence of Subang, Cirebon 1 and Cirebon 2 active fault segments will trigger earthquake which potentially liquefaction. This study aims to characterize the type of sedimentary facies induced liquefaction hazard in the lower Cimanuk catchment area, Indramayu, West Java. This research methods consist of borehole description and sedimentary facies analysis based on CPT and CPTu data with cone resistance (qt) corrected value, friction ratio (Fr), laboratory analysis and liquefaction potential based on SNI 1726:2019, which is deterministic and 2,500 years return period PGA value. Based on facies association analysis there are three facies that developed in the study area. First, delta plain facies consisting of fluvial sands, silt and clay. Second, delta front facies consisting of beach ridge sands and sandy silt. Third, silt and clay prodelta facies. Liquefaction potential analysis based on N-SPT, CPT and CPTu data shows that almost all test point are potentially liquefied, especially beach ridge sands and silty sand delta front facies. Liquefaction potential is more in the northern region of the study area, caused by the low density of sand and sandy sediments (N-SPT value < 10 or qc < 6,000 kPa).